In Vitro Growth and Development of Progenies Derived from Crossings of Several Dendrobium Accessions Under Different Media - Maulida, Desi; Yusnita, Yusnita; Hapsoro, Dwi; Agustiansyah, Agustiansyah; Karyanto, Agus; Hamiranti, Rahmadyah; Nugroho, Rizki Bagus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The objective of plant hybridization is to generate alternative superior phenotypes with the aim of decreasing the dependence on wild orchid exploitation in nature. Although interspecies crosses in Dendrobium are very likely to occur and there is a low chance of experiencing bud depression, interspecies crosses have the potential to encounter several problems, including failure of embryo development resulted to the seeds unable to germinate. Media formulation is the most essential component in the success of in vitro culture of orchid seeds. Therefore, this study aimed to obtain new Dendrobium hybrids and the best media formulation for germination and seedling growth. A total of three experiments were conducted including hybridization, the impacts of basic media namely (1) MS, (2) VW, and (3) foliar fertilizer both with and without the addition of tryptone, on seedling germination. The results showed that there was no compatibility barriers observed in all crosses. Foliar fertilizer + tryptone media was recommended for orchid seedlings because it produced better growth and roots up to 8 months after planting (MAP). For best results on Dendrobium hybrid seedlings, MS + tryptone media up to 6 MAP was used followed by deflasking into VW + tryptone to stimulate optimal root growth before hardening.